2021
DOI: 10.1080/00036846.2021.1990844
|View full text |Cite
|
Sign up to set email alerts
|

Financial contagion among COVID-19 concept-related stocks in China

Abstract: This paper investigates, for the first time, the presence of financial contagion among several important Chinese coronavirus concept-based stock indices during the recent COVID-19 global pandemic. We utilize a regime-switching skew-normal (RSSN) methodology to test for contagion through the correlation and coskewness channels while considering structural breaks in the different moments. Our results present evidence of contagion effects, which are robust across identified crisis and non-crisis periods, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 25 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…The authors used the FARM-selection approach and the time-varying financial network model and concluded that the Covid-19 outbreak increases the number of contagion channels in the international financial system. Corbet, Hou, Hu, and Oxley (2021) examined the presence of financial contagion among several Chinese coronavirus concept-based stock indices during the COVID-19 outbreak. They used a regime-switching skew-normal (RSSN) methodology to test for contagion through the correlation and channels while considering structural breaks in the different moments.…”
Section: Introductionmentioning
confidence: 99%
“…The authors used the FARM-selection approach and the time-varying financial network model and concluded that the Covid-19 outbreak increases the number of contagion channels in the international financial system. Corbet, Hou, Hu, and Oxley (2021) examined the presence of financial contagion among several Chinese coronavirus concept-based stock indices during the COVID-19 outbreak. They used a regime-switching skew-normal (RSSN) methodology to test for contagion through the correlation and channels while considering structural breaks in the different moments.…”
Section: Introductionmentioning
confidence: 99%
“…, 2019a, b), showing that there is strong evidence of explosive periods in cryptocurrency prices, suggesting however, the term bubble should be used with more caution, since the interpretation of these explosive periods as cryptocurrency bubbles requires a sufficient understanding of the fundamental value of cryptocurrencies. Corbet et al. (2022), using a regime-switching skew-normal (RSSN) methodology, investigated the presence of financial contagion amongst several important Chinese stock indices during the COVID-19 pandemic, with their results showcasing contagion effects.…”
Section: Bubbles and Contagion Effects In Cryptocurrency Marketsmentioning
confidence: 99%
“…The paper of Gronwald (2021) revisits the issue of price explosiveness in cryptocurrency markets (see also Bouri et al, 2018), showing that there is strong evidence of explosive periods in cryptocurrency prices, suggesting however, the term bubble should be used with more caution, since the interpretation of these explosive periods as cryptocurrency bubbles requires a sufficient understanding of the fundamental value of cryptocurrencies. Corbet et al (2022) Barberis and Thaler (2003) stated that "behavioural finance has two building blocks: limits to arbitrage, which argues that it can be difficult for rational traders to undo the dislocations caused by less rational traders; and psychology, which catalogues the kinds of deviations from full rationality we might expect to see". Since Keynes (1936) there has been an increasing attention in the identification on the role that sentiment has in the decision-making process of investors in financial markets.…”
Section: Bubbles and Contagion Effects In Cryptocurrency Marketsmentioning
confidence: 99%
“…Corbet et al (2022) Through a regime-switching skew-normal (RSSN) methodology, results reveal that contagion effects are present among several important Chinese stock market indices during the COVID-19 pandemic.…”
mentioning
confidence: 99%